Bacillus cereus and Bacillus thuringiensis in ready-to-eat cooked rice in Malaysia - Sandra, Afriani; Afsah Hejri, Leili; Robin, Tunung; Tuan Chilek, Tuan Zainazor; Tang, John Yew Huat; Mohamad Ghazali, Farinazleen; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Bacillus cereus (B. cereus) isolates are toxigenic and can cause food poisoning. Cooked rice is a potentially hazardous food, especially in tropical countries. The aim of this study was to determine the prevalence of B. cereus and B. thuringiensis in raw and cooked rice marketed in Selangor, Malaysia. In this research combination of Most Probable Number - Polymerase Chain Reaction (MPN-PCR) was used to detect gyrB gene in B. cereus and B. thuringiensis. Five local varieties of raw rice samples were negative for B. thuringiensis but all (100%) were positive for B. cereus. A total of 115 cooked rice samples (nasi lemak, nasi briyani, nasi ayam and nasi putih) were studied for the presence of B. cereus and B. thuringiensis. Nasi ayam was found to have the highest prevalence (100%) of B. cereus compared to nasi putih (76.2%) and nasi lemak (70.4%). Nasi briyani had the lowest prevalence (50%) of B. cereus. The frequencies of B. thuringiensis were found to be 10, 30 and 35.2 % in nasi putih and nasi ayam, nasi briyani and nasi lemak, respectively. The range of B. cereus and B. thuringiensis in the samples was from < 3 to 1100 MPN/g in different samples. Maximum number of B. cereus was observed in nasi lemak, nasi briyani and nasi putih (> 1100 MPN/g) while nasi ayam showed less contamination (460 MPN/g) with B. cereus which was significantly different (P < 0.05) from others. The number of B. thuringiensis in nasi lemak, nasi briyani, nasi putih and nasi ayam were found to be >1100, 93, 9.2 and 3.6 MPN/g, respectively.